MoS2 / Co3S4 heterojunction catalyst with mixed phase expanded layer structure as well as preparation method and application of MoS2 / Co3S4 heterojunction catalyst
By regulating the hydrothermal treatment conditions and solvents, the synthesis of MoS2/Co3S4 heterojunction catalyst with 1T/2H mixed phase solves the problems of poor conductivity of MoS2 and high cost of platinum-based electrocatalysts, significantly improving the kinetics and electrochemical properties of the hydrogen evolution reaction .
Patent Information
- Application Number
- CN202411349863.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
In the existing MoS2/Co3S4 heterojunction catalyst, MoS2 is 2H phase, and its conductivity is poor, resulting in less significant improvement in the kinetics of the hydrogen evolution reaction, and the high-cost platinum-based electrocatalyst has stability problems.
By regulating the solvent and conditions of hydrothermal treatment, the MoS2/Co3S4 heterojunction catalyst with a mixed phase expansion structure is synthesized. MoS2 is 1T/2H mixed phase, which improves electron transfer efficiency and water adsorption energy, and optimizes hydrogen Gibbs free energy .
The hydrogen evolution reaction kinetics are significantly improved, the stability and active sites of the catalyst are increased, the overpotential is reduced, and the electrochemical performance is improved.
Smart Images

Figure CN119219079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic hydrogen evolution, in particular to a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure and a preparation method and application thereof. Background Art
[0002] As a clean and environmentally friendly renewable resource, hydrogen energy is considered to be one of the ideal substitutes for traditional fossil energy. So far, people have been committed to electrolyzing water to provide hydrogen fuel, thereby promoting high-quality development and high-level protection, establishing and improving a green, low-carbon, circular economic system, and ensuring the achievement of carbon neutrality goals. However, due to the slow kinetics of the hydrogen evolution reaction (HER), in order to bypass these higher kinetic activation energy barriers and reduce its overpotential, highly active electrocatalysts are essential for HER.
[0003] Currently, platinum (Pt)-based electrocatalysts are considered to be the best candidates for water splitting due to their high activity, but their high cost and poor stability limit their widespread application. Therefore, it is necessary to prepare non-precious metal catalysts that have low cost, high activity and stability.
[0004] MoS2 has attracted wide attention due to its unique layered structure and high activity, but due to its small edge ratio and large inert basal surface, it exhibits poor HER activity. Co3S4, also a non-metallic sulfide, exhibits high activity and good stability in the electrocatalytic process, thanks to its unique structure and chemical properties. Therefore, MoS2 and Co3S4 can further adjust the HER performance through compounding and overcome the technical defect of high cost of platinum-based electrocatalysts.
[0005] Although the prior art has disclosed a method for preparing MoS2 / Co3S4 heterojunction materials, and the obtained MoS2 / Co3S4 heterojunction materials can improve the charge transfer efficiency, due to the stable structure of 2H phase MoS2, the MoS2 in the MoS2 / Co3S4 heterojunction materials obtained by the preparation method disclosed in the prior art is all 2H phase, and the phase structure of MoS2 itself is not essentially changed. Moreover, due to the poor conductivity of 2H phase MoS2, the improvement of hydrogen evolution reaction kinetics is not obvious. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expansion structure, a preparation method thereof and an application thereof. The present invention synthesizes a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expansion structure by regulating the solvent and conditions of the hydrothermal treatment. In the MoS2 / Co3S4 heterojunction catalyst, MoS2 is a 1T / 2H mixed phase and has an expansion structure. Compared with the prior art MoS2 / Co3S4 heterojunction catalyst, the present invention designs the structure of MoS2 by regulating the solvent and conditions of the hydrothermal treatment, so that the constructed MoS2 / Co3S4 heterojunction catalyst has a mixed phase expansion structure, accelerates the transfer of electrons at the interface, increases the adsorption energy of water, optimizes the hydrogen Gibbs free energy, and significantly improves the kinetics of the hydrogen evolution reaction.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for preparing a MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure comprises the following steps:
[0009] The carbon material is heat-treated under a protective atmosphere to obtain a carbon precursor, the carbon precursor is mixed with dilute nitric acid, and the carbon precursor is oxidized with the dilute nitric acid to make the surface of the carbon precursor have more oxygen-containing functional groups to obtain foamed carbon.
[0010] The carbon material is selected from melamine foam, carbon cloth, carbon paper or carbon sheet. In the present invention, melamine foam is taken as an example for research.
[0011] Soluble cobalt salt, dimethylimidazole and foam carbon are mixed. The oxygen-containing functional groups on the foam carbon are conducive to the adsorption of cobalt ions, so that the Co-MOF material can grow on the foam carbon. The material is then allowed to stand to obtain the C-Co-MOF material.
[0012] The C-Co-MOF material is first heat-treated under a protective atmosphere to improve the conductivity to obtain an intermediate, and then the intermediate is heat-treated in an air atmosphere to increase the functional groups on Co-MOF in the C-Co-MOF material for adsorbing molybdenum ions, which is beneficial to the subsequent growth of MoS2 on the Co-MOF surface to obtain a C-Co-MOF precursor.
[0013] Thiourea, Na2MoO4·2H2O and C-Co-MOF precursor are mixed in a solvent. After Co-MOF adsorbs molybdenum ions, hydrothermal treatment is performed. At this time, thiourea sulfurizes Mo and Co to obtain a MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure.
[0014] When preparing the carbon precursor, the heat treatment conditions are: heat treatment at 900°C to 1000°C for 2 hours.
[0015] Preferably, the volume ratio of the mass of the carbon precursor to the dilute nitric acid is 1:100-300. Too much dilute nitric acid will increase the functional groups on the surface of the carbon precursor. Too many functional groups adsorb a large amount of cobalt ions, making the obtained Co3S4 nanosheets too dense, which is not conducive to the subsequent growth of MoS2 nanosheets.
[0016] Preferably, when preparing the foamed carbon, the oxidation conditions are: oxidation in a nitric acid solution with a concentration of 1-3 mol / L at 100° C. to 140° C. for 2 h to 4 h.
[0017] Preferably, the mass ratio of the soluble cobalt salt, dimethylimidazole and foamed carbon is 5-20:10-40:1.
[0018] Preferably, when preparing the intermediate, the heat treatment conditions are: heating at 600° C. to 900° C. for 1 h to 3 h.
[0019] Preferably, when preparing the C-Co-MOF precursor, the heat treatment conditions are: heating at 100° C. to 300° C. for 1 h to 3 h.
[0020] Preferably, when preparing a MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure, the solvent for hydrothermal treatment consists of deionized water and anhydrous ethanol, and the volume ratio of the two is 1-3:2. This ratio is conducive to the formation of 1T phase MoS2 and increases the content of 1T phase MoS2. If the solvent does not contain ethanol, 1T phase MoS2 will not be formed.
[0021] Preferably, the hydrothermal treatment conditions are: hydrothermal treatment at 150°C to 200°C for 1h to 4h. The temperature and duration will affect the structure of MoS2. If the temperature is too high or the time is too long, the content of 1T phase MoS2 formed will be reduced; if the temperature is too low or the time is too short, the MoS2 content will be low and the crystallinity will be poor. Therefore, both temperature and time will lead to unsatisfactory catalytic performance of MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion layer structure.
[0022] Preferably, the mass ratio of thiourea, Na2MoO4·2H2O and C-Co-MOF precursor is 10-60:5-20:1.
[0023] The present invention also protects the MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure obtained by the above-mentioned preparation method. The MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure uses foam carbon as a substrate, loads Co3S4 nanosheets on the foam carbon, and grows MoS2 nanosheets on the Co3S4 nanosheets.
[0024] The present invention also protects the use of the above-mentioned MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure in the preparation of cathode materials for hydrogen production by electrolysis of water.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention oxidizes the carbon material after heat treatment under a protective atmosphere to obtain a foamed carbon whose surface is conducive to the adsorption and growth of cobalt ions, mixes the foamed carbon with a soluble cobalt salt and dimethylimidazole, constructs a C-Co-MOF material, heat treats the C-Co-MOF material twice, improves the conductivity and is also conducive to the growth of molybdenum ions on the surface of the Co-MOF material, obtains a C-Co-MOF precursor, and finally mixes the C-Co-MOF precursor, a molybdenum source and thiourea, obtains MoS2 with an extended layer structure by regulating the temperature and time of the hydrothermal treatment, obtains MoS2 with a 1T / 2H mixed phase by regulating the solvent of the hydrothermal reaction, and finally obtains a MoS2 / Co3S4 heterojunction catalyst with a mixed phase extended layer structure. The preparation method of the present invention mainly lies in the conditions and solvent regulation of the hydrothermal treatment, and then obtains MoS2 with an extended layer structure and a 1T / 2H mixed phase.
[0027] 2. In the MoS2 / Co3S4 heterojunction disclosed in the prior art, MoS2 is all in 2H phase, 2H phase MoS2 has good stability but poor conductivity, 1T phase MoS2 has poor stability but good conductivity, the present invention obtains MoS2 of 1T and 2H mixed phase, the conductivity of 1T phase is about 6-7 orders of magnitude of 2H phase, and the number of active sites exposed is more, the water adsorption capacity is improved, and it also has the optimized Gibbs free energy, all of which promote the HER performance of MoS2 / Co3S4 heterojunction catalyst with mixed phase extended layer structure, and after obtaining 1T / 2H mixed phase, the problem of poor structural stability of 1T phase MoS2 is effectively solved. The MoS2 of the present invention is an extended layer structure, and the intrinsic MoS2 interlayer spacing is about 0.62nm. Compared with the intrinsic MoS2 of the prior art, the present invention expands the interlayer spacing to about 0.93nm, which is increased by about 50%, and the expansion of the interlayer spacing also has a significant promoting effect on the improvement of HER performance.
[0028] In addition, in electrochemical reactions, Co3S4 can act as a medium for electron transfer, promoting the transfer and transmission of electrons, thereby accelerating the reaction and further improving the activity of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure.
[0029] 3. The MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion structure of the present invention has 1T and 2H mixed phases while expanding the interlayer spacing, thereby increasing the conductivity of the electrode and the number of active sites, further improving the HER catalytic performance. The results show that it exhibits excellent catalytic activity in both 1.0 mol / L KOH solution and 0.5 mol / L H2SO4 solution. -2 The overpotentials at the current densities are 85 mV and 92 mV, respectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure in Example 1.
[0031] Figure 2 Transmission electron micrographs of different positions of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure in Example 1.
[0032] Figure 3 This is the XRD diagram of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure in Example 1.
[0033] Figure 4 It is the XPS graph of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion layer structure of Example 1; wherein, Figure (a) is the XPS graph of Co, and Figure (b) is the XPS graph of Mo.
[0034] Figure 5 This is a polarization curve diagram of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure before and after it circulates 3000 times in a 1.0 mol / L KOH solution.
[0035] Figure 6 This is a polarization curve diagram of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure in Example 1 before and after circulating 3000 times in a 0.5 mol / L H2SO4 solution.
[0036] Figure 7 Polarization curves of the MoS2 / Co3S4 heterojunction catalyst with a mixed-phase expanded layer structure in Example 1, the MoS2 catalyst with a mixed-phase expanded layer structure in Comparative Example 1, and the Co3S4 catalyst in Comparative Example 2 in 1.0 mol / L KOH solution.
[0037] Figure 8Polarization curves of the MoS2 / Co3S4 heterojunction catalyst with a mixed-phase expanded layer structure in Example 1, the MoS2 catalyst with a mixed-phase expanded layer structure in Comparative Example 1, and the Co3S4 catalyst in Comparative Example 2 in 0.5 mol / L H2SO4 solution. DETAILED DESCRIPTION
[0038] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0039] Taking into account the problem of poor conductivity of 2H phase MoS2 in the prior art MoS2 / Co3S4 heterojunction material, the hydrogen evolution reaction kinetics of the obtained MoS2 / Co3S4 heterojunction material is not significantly improved. Based on this, the present invention regulates the structure and composition of MoS2 in the MoS2 / Co3S4 heterojunction material by regulating the conditions and solvent of hydrothermal treatment, and obtains MoS2 with a mixed phase expanded layer structure. The conductivity of the 1T phase is about 6-7 orders of magnitude of that of the 2H phase. The expansion of the interlayer spacing of the expanded layer structure also promotes the improvement of the HER performance, thereby overcoming the problem of the unclear HER performance of the prior art MoS2 / Co3S4 heterojunction material.
[0040] The technical solution of the present invention is further explained by using embodiments and comparative examples below. The specific research method is as follows:
[0041] Example 1
[0042] A method for preparing a MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure comprises the following steps:
[0043] (1) Melamine foam was heat treated at 900° C. for 2 h in an argon atmosphere to obtain a carbon precursor, the carbon precursor was placed in a high-pressure reactor, 40 mL of 3 mol / L dilute nitric acid was poured into it, and foamed carbon was obtained after hydrothermal treatment at 120° C. for 3 h.
[0044] (2) 436.5 mg of Co(NO3)2·6H2O and 975 mg of dimethylimidazole (C4H6N2) were dissolved in 38 mL of deionized water respectively. After magnetic stirring for 30 min, the Co(NO3)2·6H2O solution was poured into the C4H6N2 solution to obtain a mixed solution. Then 20 g of foamed carbon was placed in the mixed solution and left at room temperature for 4 h to obtain C-Co-MOF material.
[0045] (3) The C-Co-MOF material was placed in a tubular furnace, the heating rate was set to 5°C / min, and heat treated at 750°C in an argon atmosphere for 2 h to obtain an intermediate. The intermediate was then further heat treated in a tubular furnace at 200°C in an air atmosphere for 1 h to obtain a C-Co-MOF precursor.
[0046] (4) Pour 761.25 mg of thiourea into a mixed solution of deionized water and anhydrous ethanol, stir for 10 min, then add 287.95 mg of Na2MoO4·2H2O and 20 mg of C-Co-MOF precursor, stir for 30 min, place in a high pressure reactor, hydrothermally treat at 200 °C for 4 h, wash with water, and dry to obtain a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure.
[0047] The volume ratio of deionized water to anhydrous ethanol is 3:2.
[0048] Example 2
[0049] A method for preparing a MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure comprises the following steps:
[0050] (1) Melamine foam was heat treated at 1000° C. for 2 h in an argon atmosphere to obtain a carbon precursor, the carbon precursor was placed in a high-pressure reactor, 40 mL of 2 mol / L dilute nitric acid was poured into it, and foamed carbon was obtained after hydrothermal treatment at 100° C. for 4 h.
[0051] (2) 436.5 mg of Co(NO3)2·6H2O and 1462.5 mg of dimethylimidazole (C4H6N2) were dissolved in 38 mL of deionized water respectively. After magnetic stirring for 30 min, the Co(NO3)2·6H2O solution was poured into the C4H6N2 solution to obtain a mixed solution. Then 43.6 g of foamed carbon was placed in the mixed solution and left at room temperature for 4 h to obtain C-Co-MOF material.
[0052] (3) The C-Co-MOF material was placed in a tubular furnace, the heating rate was set to 5°C / min, and heat treated at 900°C in an argon atmosphere for 1 h to obtain an intermediate. The intermediate was then further heat treated in a tubular furnace at 100°C in an air atmosphere for 3 h to obtain a C-Co-MOF precursor.
[0053] (4) Pour 761.25 mg of thiourea into a mixed solution of deionized water and anhydrous ethanol, stir for 10 min, then add 350 mg of Na2MoO4·2H2O and 76 mg of C-Co-MOF precursor, stir for 30 min, place in a high pressure reactor, hydrothermally treat at 100 °C for 2 h, wash with water, and dry to obtain a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure.
[0054] The volume ratio of deionized water to anhydrous ethanol is 1:1.
[0055] Example 3
[0056] A method for preparing a MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure comprises the following steps:
[0057] (1) Melamine foam is heat-treated at 950° C. for 2 h in an argon atmosphere to obtain a carbon precursor, the carbon precursor is placed in a high-pressure reactor, 40 mL of 1 mol / L dilute nitric acid is poured into it, and foamed carbon is obtained after hydrothermal treatment at 140° C. for 2 h.
[0058] (2) 436.5 mg of Co(NO3)2·6H2O and 975 mg of dimethylimidazole (C4H6N2) were dissolved in 38 mL of deionized water respectively. After magnetic stirring for 30 min, the Co(NO3)2·6H2O solution was poured into the C4H6N2 solution to obtain a mixed solution. Then 44 g of foamed carbon was placed in the mixed solution and left at room temperature for 4 h to obtain a C-Co-MOF material.
[0059] (3) The C-Co-MOF material was placed in a tubular furnace, the heating rate was set to 5°C / min, and heat treated at 600°C in an argon atmosphere for 3 h to obtain an intermediate. The intermediate was then further heat treated in a tubular furnace at 300°C in an air atmosphere for 2 h to obtain a C-Co-MOF precursor.
[0060] (4) Pour 761.25 mg of thiourea into a mixed solution of deionized water and anhydrous ethanol, stir for 10 min, then add 253.75 mg of Na2MoO4·2H2O and 12.68 mg of C-Co-MOF precursor, stir for 30 min, place in a high pressure reactor, hydrothermally treat at 200 °C for 3 h, wash with water, and dry to obtain a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure.
[0061] The volume ratio of deionized water to anhydrous ethanol is 1:2.
[0062] Example 4
[0063] A method for preparing a MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure comprises the following steps:
[0064] (1) Melamine foam is heat-treated at 950° C. for 2 h in an argon atmosphere to obtain a carbon precursor, the carbon precursor is placed in a high-pressure reactor, 40 mL of 2 mol / L dilute nitric acid is poured into it, and foamed carbon is obtained after hydrothermal treatment at 130° C. for 2 h.
[0065] (2) 436.5 mg of Co(NO3)2·6H2O and 1018.5 mg of dimethylimidazole (C4H6N2) were dissolved in 38 mL of deionized water respectively. After magnetic stirring for 30 min, the Co(NO3)2·6H2O solution was poured into the C4H6N2 solution to obtain a mixed solution. Then 29 g of foamed carbon was placed in the mixed solution and left at room temperature for 4 h to obtain a C-Co-MOF material.
[0066] (3) The C-Co-MOF material was placed in a tubular furnace, the heating rate was set to 5°C / min, and heat treated at 800°C in an argon atmosphere for 2.5 h to obtain an intermediate. The intermediate was then further heat treated in a tubular furnace at 250°C in an air atmosphere for 1 h to obtain a C-Co-MOF precursor.
[0067] (4) Pour 761.25 mg of thiourea into a mixed solution of deionized water and anhydrous ethanol, stir for 10 min, then add 152.25 mg of Na2MoO4·2H2O and 15.2 mg of C-Co-MOF precursor, stir for 30 min, place in a high pressure reactor, hydrothermally treat at 200 °C for 3 h, wash with water, and dry to obtain a MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure.
[0068] The volume ratio of deionized water to anhydrous ethanol is 1:2.
[0069] Comparative Example 1
[0070] The preparation method of the MoS2 catalyst having a mixed phase expanded layer structure is the same as the preparation steps of Example 1, except that the mass of Co(NO3)2·6H2O is reduced from 436.5 mg to 0 mg, and the mass of dimethylimidazole is reduced from 975 mg to 0 mg, and comprises the following steps:
[0071] (1) Melamine foam was heat treated at 900° C. for 2 h in an argon atmosphere to obtain a carbon precursor, the carbon precursor was placed in a high-pressure reactor, 40 mL of 3 mol / L dilute nitric acid was poured into it, and foamed carbon was obtained after hydrothermal treatment at 120° C. for 3 h.
[0072] (2) Pour 761.25 mg of thiourea into a mixed solution of deionized water and anhydrous ethanol, stir for 10 min, then add 287.95 mg of Na2MoO4·2H2O and 20 mg of foamed carbon, stir for 30 min, place in a high pressure reactor, hydrothermally treat at 200°C for 4 h, wash with water, and dry to obtain a MoS2 catalyst with a mixed phase expanded layer structure.
[0073] The volume ratio of deionized water to anhydrous ethanol is 3:2.
[0074] Comparative Example 2
[0075] The preparation method of the Co3S4 catalyst is the same as the preparation steps of Example 1, except that the mass of Na2MoO4·2H2O is reduced from 287.95 mg to 0 mg, and comprises the following steps:
[0076] (1) Melamine foam was heat treated at 900° C. for 2 h in an argon atmosphere to obtain a carbon precursor, the carbon precursor was placed in a high-pressure reactor, 40 mL of 3 mol / L dilute nitric acid was poured into it, and foamed carbon was obtained after hydrothermal treatment at 120° C. for 3 h.
[0077] (2) 436.5 mg of Co(NO3)2·6H2O and 975 mg of dimethylimidazole (C4H6N2) were dissolved in 38 mL of deionized water respectively. After magnetic stirring for 30 min, the Co(NO3)2·6H2O solution was poured into the C4H6N2 solution to obtain a mixed solution. Then 20 g of foamed carbon was placed in the mixed solution and left at room temperature for 4 h to obtain C-Co-MOF material.
[0078] (3) The C-Co-MOF material was placed in a tubular furnace, the heating rate was set to 5°C / min, and heat treated at 750°C in an argon atmosphere for 2 h to obtain an intermediate. The intermediate was then further heat treated in a tubular furnace at 200°C in an air atmosphere for 1 h to obtain a C-Co-MOF precursor.
[0079] (4) Pour 761.25 mg of thiourea (CH4N2S) into a mixed solution of deionized water and anhydrous ethanol, stir for 10 min, add 20 mg of C-Co-MOF precursor, place in a high-pressure reactor, hydrothermally treat at 200 °C for 4 h, wash with water, and dry to obtain a Co3S4 catalyst.
[0080] The volume ratio of deionized water to anhydrous ethanol is 3:2.
[0081] Examples 1-4 of the present invention all prepared MoS2 / Co3S4 heterojunction catalysts with a mixed phase expansion structure and high hydrogen evolution reaction kinetics. The MoS2 / Co3S4 heterojunction catalyst with a mixed phase expansion structure prepared in Example 1 is used as an example for research, and is compared with Comparative Examples 1-2. The specific research methods and results are as follows:
[0082] Figure 1 The results show that MoS2 nanosheets are vertically cross-arranged on the carbon foam, and MoS2 nanosheets grow on Co3S4 nanosheets.
[0083] Figure 2 The results in the middle left figure show that the MoS2 / Co3S4 heterojunction catalyst with a mixed phase extended layer structure has two different lattice fringes, with lattice spacings of 0.28nm and 0.92nm, corresponding to the (311) crystal plane of Co3S4 and the (002) crystal plane of MoS2, respectively, indicating that MoS2 with an extended layer structure was synthesized. In addition, a heterogeneous interface was formed between MoS2 and Co3S4, proving that the MoS2 / Co3S4 heterojunction was successfully synthesized. At the same time, Figure 2 The middle right figure shows that MoS2 exists in both the 2H phase with triangular prism coordination and the 1T phase with octahedral coordination, thus confirming the existence of the 1T / 2H phase.
[0084] Figure 3 The results show that all the diffraction peaks of Co3S4 are consistent with the standard card (JCPDS NO.47-1738), indicating that Co3S4 was successfully obtained after sulfurization of the C-Co-MOF precursor. As for MoS2, the (002) crystal plane corresponding to the MoS2 / Co3S4 heterojunction at 2θ of 14.46° deviates to 9.7°, indicating that the interplanar spacing is extended from 0.64nm to 0.92nm, indicating that the synthesized MoS2 has an extended interlayer spacing.
[0085] Figure 4 The results show that the two peaks at 229.35eV and 232.58eV in the Mo3d spectrum correspond to the 2H phase in the MoS2 / Co3S4 heterostructure, and the two peaks at 228.67eV and 232.01eV correspond to the Mo3d phase in the 1T phase of MoS2. 5 / 2 and Mo3d 3 / 2 orbitals, indicating that MoS2 in MoS2 / Co3S4 is a 1T / 2H mixed phase. In the Co2p energy spectrum, the two peaks at 797.79eV and 781.59eV correspond to Co 2+ , the two peaks at 793.89eV and 778.86eV correspond to Co 3+ .
[0086] The electrochemical performance of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure is tested below. Since the MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure has a unique three-dimensional structure, it can be directly used as a working electrode.
[0087] The test method is as follows:
[0088] Figure 5-Figure 8 The detection method is as follows: an electrochemical workstation is used for scanning, in a 1 mol / L KOH solution, a carbon rod is used as a counter electrode, a saturated calomel electrode is used as a reference electrode, a MoS2 / Co3S4 heterojunction catalyst with a mixed phase extended layer structure, a MoS2 catalyst with a mixed phase extended layer structure, or a Co3S4 catalyst is used as a working electrode, the counter electrode, the reference electrode, and the working electrode are assembled into a three-electrode system, and the electrochemical performance of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase extended layer structure is evaluated.
[0089] In 0.5 mol / L H2SO4 solution, with a carbon rod as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a MoS2 / Co3S4 heterojunction catalyst with a mixed phase extended layer structure, a MoS2 catalyst with a mixed phase extended layer structure, or a Co3S4 catalyst as the working electrode, the counter electrode, the reference electrode and the working electrode were assembled into a three-electrode system, and the electrochemical properties of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase extended layer structure were evaluated.
[0090] Figure 5 The results show that when the current density is 10 mA cm -2 Under the condition of 100% mol / l, the overpotential of the MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion layer structure is only 85 mV, which proves that it has good catalytic performance in alkaline solution. At the same time, the polarization curve after 3000 CV test cycles shows a very small negative potential shift, indicating that the MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion layer structure has excellent cycle stability in alkaline medium.
[0091] Figure 6 The results show that when the current density is 10 mA cm -2 Under the condition of low temperature, the overpotential of the MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion layer structure is only 92mV, which proves that it has good catalytic performance in acidic solution. At the same time, after 3000 CV cycle tests, the overpotential of the LSV curve shows only a negligible increase, which proves that the MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion layer structure has excellent cycle stability in acidic medium.
[0092] Figure 7The results show that in alkaline medium, when the current density is 10 mA cm -2 Under this condition, the overpotential of the MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion structure is only 85mV (η 10 =85mV), which has good catalytic performance. However, both MoS2 and Co3S4 showed poor HER performance, among which MoS2 has a low η 10 is 112mV, and the η of Co3S4 10 It is 126 mV, indicating that the construction of heterostructure can effectively improve the HER catalytic activity.
[0093] Figure 8 The results show that in acidic medium, when the current density is 10 mA cm -2 Under this condition, the overpotential of the MoS2 / Co3S4 heterojunction catalyst with mixed phase expansion structure is only 92mV (η 10 =92mV), which has good catalytic performance. However, both MoS2 and Co3S4 showed poor HER performance. 10 is 185mV, and the η of Co3S4 10 It is 246 mV, indicating that the construction of heterostructure can effectively improve the HER catalytic activity.
[0094] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure, characterized in that: The steps include: The carbon material is subjected to heat treatment under a protective atmosphere to obtain a carbon precursor, and the carbon precursor is oxidized to obtain foamed carbon; A soluble cobalt salt, dimethylimidazole and foamed carbon are mixed, and the oxygen-containing functional groups on the surface of the foamed carbon are used to adsorb cobalt ions, and then the mixture is allowed to stand to obtain a C-Co-MOF material; The C-Co-MOF material is first heat-treated in a protective atmosphere to improve the conductivity to obtain an intermediate, and then the intermediate is heat-treated in an air atmosphere to increase the functional groups on Co-MOF in the C-Co-MOF material for adsorption to obtain a C-Co-MOF precursor; Thiourea, a soluble molybdenum source and a C-Co-MOF precursor are mixed in a solvent, and after Co-MOF adsorbs molybdenum ions, a hydrothermal treatment is performed to obtain a MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion structure; The solvent for the hydrothermal treatment is composed of deionized water and anhydrous ethanol, and the volume ratio of the two is 1-3:2; The conditions of the hydrothermal treatment are: hydrothermal treatment at 150°C to 200°C for 1h to 4h.
2. The method for preparing the MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure according to claim 1, characterized in that: The mass ratio of thiourea, Na2MoO4·2H2O and C-Co-MOF precursor is 10-60:5-20:
1.
3. The method for preparing the MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure according to claim 1, characterized in that: The mass ratio of soluble cobalt salt, dimethylimidazole and foamed carbon is 5-20:10-40:
1.
4. The method for preparing the MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure according to claim 1, characterized in that: When preparing the intermediate, the heat treatment conditions are: heating at 600°C to 900°C for 1h to 3h.
5. The method for preparing the MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure according to claim 1, characterized in that: When preparing the C-Co-MOF precursor, the heat treatment conditions are: heating at 100°C to 300°C for 1h to 3h.
6. The method for preparing the MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure according to claim 1, characterized in that: When preparing the carbon precursor, the heat treatment conditions are: heat treatment at 900°C to 1000°C for 2 hours.
7. The method for preparing the MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure according to claim 1, characterized in that: The oxidation conditions are: oxidation in a nitric acid solution with a concentration of 1-3 mol / L at 100°C to 140°C for 2h to 4h.
8. A MoS2 / Co3S4 heterojunction catalyst having a mixed phase expanded layer structure obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The MoS2 / Co3S4 heterojunction catalyst with a mixed phase diffusion layer structure uses foam carbon as a substrate, loads Co3S4 nanosheets on the foam carbon, and grows MoS2 nanosheets on the Co3S4 nanosheets.
9. Use of the MoS2 / Co3S4 heterojunction catalyst with a mixed phase expanded layer structure as claimed in claim 8 in the preparation of cathode materials for hydrogen production by electrolysis of water.